Kesantunan Berbahasa Dalam Cerita Bersambung Mikul dhuwur Mendhem Jero Karya Tiyasti Dalam Majalah Djaka Lodang Tahun 2017 - Hikmah, Anirotul; Aryanto, Aris; Widiyono, Yuli; Setyowati, Herlina (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to describe (1) compliance with the principle of politeness in language, and (2) violation of the principle of politeness in language in the serialized story Mikul Dhuwur Mendhem Jero by Tiyasti. This type of research is descriptive qualitative. The data source of this research is the serialized story of Mikul Dhuwur Mendhem Jero by Tiyasti. The data of this research are quotations that contain compliance with the principles of politeness in language and violations of the principles of politeness in the serialized story of Mikul Dhuwur Mendhem Jero by Tiyasti. Data collection techniques using library techniques and see notes. The research instrument is the researcher himself as the main instrument. Data analysis using content analysis techniques. The results of the study: The forms of compliance with the principles of politeness in language include: (a) 15 maxims of wisdom; (b) 4 maxims of generosity; (c) 11 maxims of praise; (d) 10 humility maxims; (e) 11 agreement maxims; and (f) 6 sympathy maxims. Forms of violation of language politeness include: (a) 2 maxims of wisdom; (b) 3 maxims of praise; (c) 1 humility maxim; (d) 3 maxims of agreement. In the serialized story Mikul Dhuwur Mendhem Jero by Tiyasti, there is no violation of the maxim of generosity and maxim of sympathy.